1992
DOI: 10.1159/000168498
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Immune Deposits with EDTA Chelation Therapy in a Case of IgA Nephropathy

Abstract: In this report, we describe the development of renal function impairment in a 33-year-old patient with mesangial IgA nephropathy and a history of recent gout. Increased body lead burden was identified with a positive EDTA mobilization test. The patient was treated with 1 g of edetate disodium calcium weekly for 2 months until normalization of urinary lead excretion. Improvement of renal function and proteinuria were noted. It was even more interesting to find that both immunofluorescence and electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The EDTA chelating agent is safe in treating patients with CRI with a smaller dose and a longer interval. 3,9,12,24 Wedeen et al 25 extensively used EDTA as test doses in large numbers of patients and as therapy in a smaller number, yet they never encountered any evidence of nephrotoxicity. The same findings were also noted in previous studies.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations
“…The EDTA chelating agent is safe in treating patients with CRI with a smaller dose and a longer interval. 3,9,12,24 Wedeen et al 25 extensively used EDTA as test doses in large numbers of patients and as therapy in a smaller number, yet they never encountered any evidence of nephrotoxicity. The same findings were also noted in previous studies.…”
Section: Commentmentioning
confidence: 99%
“…The same findings were also noted in previous studies. [2][3][4][9][10][11][12][13]16 Hence, the EDTA chelation therapy might be a better alternative to treat patients with progressive renal insuffi- Kaplan-Meier estimates of primary renal outcome in patients with chronic renal insufficiency who had high-normal (Ն80 µg and Ͻ600 µg) and low (Ͻ80 µg) body lead burdens (BLBs) (PϽ.001 by log-rank test). ciency.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…(19)(20)(21) Lin et al conducted EDTA mobilisation tests to assess the body burden of lead in patients with different degrees of renal insufficiency and no known lead exposure; their results suggest that long-term, low-level environmental lead exposure may be associated with the progression of renal insufficiency. (8,9) They also showed that long-term, low-level environmental lead exposure may be associated with renal tubular and glomerular damage in patients with immunoglobulin A nephropathy (22) and in residents who had been living near a lead battery factory for more than ten years. (23) The findings of these studies suggest that there may be a positive association between long-term lead exposure (resulting in a high body burden of lead) and impaired kidney function.…”
Section: Discussionmentioning
confidence: 99%